Mechanical Characteristics of Biocomposites Based on Rice Husk Reinforced Recycled Polypropylene - Tezara Cionita; Jaafar, Jamiluddin; Siregar, Januar Parlaungan; Syed Abdul Karim, Syed Mohd Amri; Zulkiflee, Mohamad Fadhlin; Shamsuddin, Muhammad Izuddin; Junid, Ramli; Deni Fajar Fitriyana; Al Ichlas Imran; Mohamad Hamdan, Mohammad Hazim (International Journal of Integrated Engineering, 2024)
This work aims to investigate the influence of the combination of rice husk (RH) and recycled polypropylene (RPP) in producing environmentally friendly materials. In the current investigation, four distinct compounds were selected to identify the most effective combination for achieving the highest result of mechanical properties outcomes. Samples were created with variable RH concentrations (10%, 20%, 30%, and 40% by weight). The results showed that RH-RPP with 20% of RH had the highest mechanical properties. Scanning electron microscopy (SEM) images prove the enhanced mechanical characteristics. In addition, the water absorption and thickness swelling analysis show that RH-RPP composites with 20% RH concentration produce competitive results of 1.14% and 2.06%, respectively. Therefore, the finding from the present study summarized that the combination of RH and RPP with 20% of RH percentage had a great potential in producing competitive eco-friendly material for engineering applications. In addition, it is anticipated that it will be able to create RH-RPP composites as a potential alternative for conventional polymers in various applications, thereby contributing to sustainable development goals especially in line with the SDG 12, responsible consumption and production.